On the Origin of the Warburg Effect in Cancer Cells: Controlling Cancer as a Metabolic Disease - Bahrami, Hassan (Asian Pacific Journal of Cancer Biology, 2024)
Background: Human cells may switch metabolism from aerobic to anaerobic or vice versa depending on cellular conditions. The use of anaerobic cellular respiration is especially common in cells with metabolic disorders such as cancer cells. However, despite the fact that metabolic alteration in cancer cells is well-established, its cause is still not well understood. Objective: The purpose of this study is to address the origin of abnormal behavior and metabolic changes in cancer cells to better understand the processes that are involved in the formation and spread of cancer. Methods: This paper reviews and explains key concepts related to the evolutionary origin of key metabolic pathways in cancer cells, considering the behavioral similarities between cancer cells and ancient unicellular organisms. The evaluations help better understand the Warburg effect and the related cancer control strategies. Results: The risk of cancer may be reduced by creating suitable and optimal conditions at the cellular level, which can increase the chance of cell survival in the event of cellular stress. This may be achieved through dietary and lifestyle modifications, such as adopting a balanced natural diet that meets cellular needs in a way that leads to cancer control. Conclusions: Understanding the biological origin and causes of cancer initiation and development is essential for the metabolic control of cancer as well as for improving therapeutic strategies.